Psychosocial And Cultural Determinants Of Resilience Among Clinically Stable Breast Cancer Survivors Post-Chemotherapy In A Tertiary Care Setting In Ghana - Gbande, S.; Ohene, L.A.; Aziato, L. (BMC Women's Health, 2026)
Background Breast cancer remains a leading cause of mortality among women in Africa. Many patients present at advanced stages because of limited awareness and restricted access to timely healthcare, contributing to elevated mortality rates and considerable psychosocial distress. Aim This study investigated the psychosocial and cultural determinants of resilience among women who survived breast cancer following chemotherapy in a tertiary care setting in Ghana. It addresses a research gap concerning the influence of cultural and psychosocial factors on survival. Methods This study employed a qualitative descriptive design. Fourteen breast cancer survivors were purposively sampled between January and March 2018. In-depth data were collected through semi-structured interviews in English. Selection bias related to language was purposively minimized. Data collection and analysis occurred concurrently, and content analysis was used to interpret the results. Results The data analysis identified four themes and eight subthemes. The themes included psychosocial support systems, cultural beliefs and practices, personal coping strategies and meaning-making, and socioeconomic and environmental factors. Conclusion This study highlighted the multifaceted and highly individualized experiences of women who received chemotherapy for breast cancer in resource-limited settings in Ghana. The findings indicated that psychosocial support from families, peers, and compassionate healthcare providers substantially strengthens emotional resilience. Furthermore, cultural and spiritual beliefs are essential for coping, as they provide meaning and emotional stability during physical distress. Personal growth, optimism, and adaptive coping strategies also enabled the women to reinterpret their illness experiences in a more positive light.
Research Article
Keywords: Breast Cancer; Cultural Determinants; Psychosocial; Resilience; Survivors; Post-Chemotherapy Women